Growth or stagnation? Farming in England, 1200–18001. (22nd June 2017) - Clark, Gregory
Abstract: Estimates of English income in Broadberry et al.'s British economic growth, 1270–1870 are founded upon a fourfold growth of farm output, and output per farm worker, over this interval. This article shows, using four separate tests, that farm output growth must have been much more limited. The tests are, first, whether in 1300 there was enough work at harvest to employ all the labour force; second, whether the value of output per worker in agriculture was greater than the annual earnings of workers; third, whether the implied relative outputs per acre of arable versus pasture were reasonable; and fourth, whether a much shorter medieval work year was possible. An alternative index of farm output consistent with the labour supply, wages, and farm rents is derived. This shows much less growth during the period 1270–1800. Overall economic growth in England during these years must consequently have been far less than Broadberry et al. estimate.